The role of resilience and coping among Italian healthcare workers during the COVID-19 pandemic - Marcolongo, Federica; Ottaviani, Marco; Romano, Paola; Bonassi, Stefano; Garramone, Ada; Infarinato, Francesco; Patrizia Russo; Tamburrano, Andrea; Tomino, Carlo; Prinzi, Giulia (La Medicina del Lavoro, 2021)
Objective: To evaluate the psychological state of healthcare workers (HCWs) in the field of rehabilitation during the COVID-19 pandemic. Methods: Cross-sectional observational study. Sample of 334 HCWs including: nurses, medical doctors, therapists, scientists, and clerical workers working at the IRCCS San Raffaele Roma rehabilitation hospital during the second wave of the COVID-19 pandemic. Anonymous web-based questionnaire included 14-item Resilience Scale, Brief-COPE, Hospital Anxiety Depression Scale, Fear of COVID-19 Scale. Occupational and sociodemographic characteristics. Results: High levels of resilience, low levels of anxiety, depression, and fear were observed in the study population; the most frequently used coping strategies in the Brief-COPE were acceptance, planning, and active coping. Specifically, 87% of the participants reported a moderate to high level of resilience, with the highest level observed in nurses while physicians show the lowest level. HCWs showed symptoms of anxiety (29%), depressive symptoms (10%), and fear caused by the COVID-19 pandemic (44%). Statistically significant differences were observed between different occupations for fear (p <0.05) and resilience (p <0.01). Levels of anxiety and fear appeared to be higher in female and younger workers. The latter group - who also reported higher levels of depression - showed lower levels of resilience. Conclusions: In our study hospital and non-hospital workers show different emotional, cognitive, and behavioural resources when facing stressful situations, like in the case of the SARS-CoV-2 pandemics. Our results support the role of resilience and the proper use of problem-focused and emotion-focused coping strategies as protective factors from psychological distress.